2011
DOI: 10.1007/s00248-011-9913-9
|View full text |Cite
|
Sign up to set email alerts
|

Community Structure of Planktonic Fungi and the Impact of Parasitic Chytrids on Phytoplankton in Lake Inba, Japan

Abstract: Freshwater fungi have received little attention by scientific research in recent years, especially fungi of the pelagic zone. Recently, parasitic fungi, termed chytrids, have been found to play important roles in aquatic food webs. Yet, the diversity and community structure of planktonic fungi including chytrids are not well studied. In this study, we examined the temporal fluctuations of freshwater fungi, including chytrids, in Lake Inba by using molecular techniques of denaturing gradient gel electrophoresis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 31 publications
2
37
0
Order By: Relevance
“…A similar study performed by Kagami et al [35], which employed DGGE and sequence analysis, demonstrated that a large proportion of the sequences belonged to chytrids in Inba Lake in Japan. Microscopic observations revealed that chytrids infect various algal species, such as Aulacoseira granulata and A. ambigua [35]. This observation is also in agreement with other work performed on high-elevation soils [31].…”
Section: Discussionmentioning
confidence: 58%
“…A similar study performed by Kagami et al [35], which employed DGGE and sequence analysis, demonstrated that a large proportion of the sequences belonged to chytrids in Inba Lake in Japan. Microscopic observations revealed that chytrids infect various algal species, such as Aulacoseira granulata and A. ambigua [35]. This observation is also in agreement with other work performed on high-elevation soils [31].…”
Section: Discussionmentioning
confidence: 58%
“…Chytrids produce motile dispersing life stages know as zoospores, are either saprotrophic or parasitic and are important contributors to aquatic food chains and carbon cycling (reviewed by Gleason et al, 2008). Despite high infection rates in natural algae populations, it is unclear how severe the effect of parasitic chytrids is (e.g., Kagami et al, 2011), however their impact may be amplified in commercial settings. For example, the chytrid Phlyctidium scenedesmi has been noted to cause severe production loss of Scenedesmus in open pond systems (Fott, 1967; Ilkov, 1975).…”
Section: Review Of Some Known Algae Parasitesmentioning
confidence: 99%
“…Fungi do exist as small zoosporic (lower) fungi known to parasitize on planktonic organisms (e.g., [7]–[9]). While it has been noted that lower fungi can also act as primary decomposers (listed by substrates in [10]) this has been rarely considered relevant until recently [11][13]. Therefore, little is known about fungal contributions to the degradation of fine particulate organic matter (FPOM) derived from algae, zooplankton, shredder activities, or other sources in the pelagic zone.…”
Section: Introductionmentioning
confidence: 99%